2006
DOI: 10.1017/s0144686x05004654
|View full text |Cite
|
Sign up to set email alerts
|

Older people's views on how to finance increasing health-care costs

Abstract: The aims of this paper are to investigate both older people's views about ways in which to finance health-care costs and their willingness to pay for treatment themselves, along with variations in these views by age and gender. The data are from the Good Ageing in Skåne (GAS) prospective longitudinal cohort study in Sweden, which involved medical examinations and a survey of living arrangements and socio-economic conditions. For the analysis reported in this paper, 930 GAS respondents aged 60-93 years were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Studies have shown that people aged 60 and over are willing to pay for treatment to avoid waiting lists if they are in a financial situation that allows them to do so (6,14). The results of Werntoft et al (6) nevertheless showed that the oldest-old, 85 years and over, were more likely to chose staying on waiting lists than people under 85, although their financial situation was considered equal to that of the others.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Studies have shown that people aged 60 and over are willing to pay for treatment to avoid waiting lists if they are in a financial situation that allows them to do so (6,14). The results of Werntoft et al (6) nevertheless showed that the oldest-old, 85 years and over, were more likely to chose staying on waiting lists than people under 85, although their financial situation was considered equal to that of the others.…”
Section: Introductionmentioning
confidence: 67%
“…This is in line with the results from earlier studies involving people aged 60 and over, based on a structured questionnaire concerning prioritisation and resource allocation. The participants did not want age to be a criterion in prioritisation, and if they could afford it, they were willing to pay to get treatment at once instead of being on a waiting list (5,6). In order to increase the understanding of their standpoints it seems important to investigate how older people reason about prioritisation in health care.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of women, there seemed to be an association with their poorer financial situation. The result also showed that 72 % of the participants wanted to increase general taxation and taxes on alcohol and tobacco to finance increasing healthcare costs [7]. However, we still have limited knowledge about decision makers' views on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…The questions were developed in relation to diseases occurring in old age that fall within the scope of feasible treatments, and diseases related to lifestyle. The questionnaire was tested in a pilot study [10] and was earlier used to explore older people's views concerning prioritisation and resource allocation in healthcare [7]. Some adjustments were made for this study to fit the target group, for instance regarding the question about being on a waiting list or paying to receive immediate surgery.…”
Section: The Questionnairementioning
confidence: 99%
See 1 more Smart Citation